2010
DOI: 10.1016/j.tox.2010.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oral toxicity and safety of pentamethylchromanol (PMCol), a potential chemopreventative agent, in rats and dogs

Abstract: 2,2,5,7, was administered by gavage in rats for 28 days at dose levels of 0, 100, 500, and 2000 mg/kg/day. PMCol administration induced decreases in body weight gains and food consumption, hepatotoxicity (increased TBILI, ALB, ALT, TP; increased relative liver weights; increased T4 and TSH), nephrotoxicity (increased BUN and BUN/CREAT, histopathology lesions), effect on lipid metabolism (increased CHOL), anemia, increase in WBC counts (total and differential), coagulation (FBGN↑and PT↓) and hyperkeratosis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 9 publications
0
11
1
Order By: Relevance
“…Rats were administered vehicle or PMCol by once daily oral gavage at a volume of 10 ml/kg/day and at concentrations of 0, 200, and 2000 mg/kg/day. Selection of these doses was based on the results of the previous toxicity study in rats (Lindeblad et al, 2010a), which indicated that the two doses, 200 and 2000 mg/kg, would cause adverse effects in the target tissues in a dose-dependent manner, optimizing the likelihood of identification of an early marker for hepatotoxicity and nephrotoxicity. The vehicle and high-dose groups were euthanized on day 8 (n ¼ 6 rats/group).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were administered vehicle or PMCol by once daily oral gavage at a volume of 10 ml/kg/day and at concentrations of 0, 200, and 2000 mg/kg/day. Selection of these doses was based on the results of the previous toxicity study in rats (Lindeblad et al, 2010a), which indicated that the two doses, 200 and 2000 mg/kg, would cause adverse effects in the target tissues in a dose-dependent manner, optimizing the likelihood of identification of an early marker for hepatotoxicity and nephrotoxicity. The vehicle and high-dose groups were euthanized on day 8 (n ¼ 6 rats/group).…”
Section: Methodsmentioning
confidence: 99%
“…The toxicity of PMCol has been studied in both rats and dogs after 28 days of oral dose administration as part of a preclinical development program to advance PMCol as a cancer chemopreventive agent (Lindeblad et al, 2010a(Lindeblad et al, , 2010b. These studies demonstrated that daily administration of the drug candidate resulted in pronounced toxicity in both species.…”
mentioning
confidence: 99%
“…Changes in the body weight were daily monitored during the entire study. (Lindeblad et al, 2010;OECD, 2008). At the end of the treatments, mice were euthanized placing them in a carbon dioxide camera, then mice were beheaded and blood samples were obtained for biochemical analysis, kidney, spleen and liver were obtained for histological analysis.…”
Section: Sub-acute Toxicitymentioning
confidence: 99%
“…The table draws attention to the magnitude of the response for those biomarkers that are most altered. Lindeblad et al 2010). In this case, the means and SDs are not shown as it is assumed that these will be given in accompanying tables as is usual at present.…”
Section: Tablesmentioning
confidence: 99%
“…The box plot shows more clearly the increased variation as the dose group increases: evidence of toxicity. The authors TABLE 2.-SESs for 34 biomarkers and 3 dose levels (100, 500, and 2,000 mg/kg/day of pentamethylchromanol administered to rats and sorted by the top dose level (Lindeblad et al 2010 Table 1 shown graphically (Matsuo et al 2012). Note that the axes have been exchanged in order to accommodate the biomarker labels, and 23 points have been omitted, as in the table.…”
Section: Line Plots and Box Plotsmentioning
confidence: 99%